Implementasi Tasawuf Akhlaki Dalam Pendidikan Islam - Samsudin (STIT Muslim Asia Afrika, 2022)
Sufism is a branch of knowledge in Islamic studies which is studied from time to time and has experienced rapid development so that it becomes a scientific discipline that is not only related to self-cleaning efforts (tazkiyatun nafs) to draw closer to Allah as Al-Khaliq so as to lead a person to ma'rifatullah, but the development of Sufism has also become a scientific discipline that is closely related to one of the ways to improve morals in people's lives or in other words tasawuf is not only an effort to cleanse oneself individually but also how to build a society of good morals through Islamic Religious Education. One of the approaches in the study of Sufism is the Sufism of morality. Sufism of morality is tasawuf which prioritizes the improvement of morals. The teachings of tasawuf akhlaki emphasize the amaliyahs to obtain perfection and purity of the soul which are based on improving mental attitudes which are carried out with a strict level of behavioral discipline, through consistent training (riyadhoh) to achieve moral perfection - perfect human beings. Seeing the development of today's modern society which is experiencing a crisis and moral decadence due to liberal life and the hedonism of the teachings of Sufism and morality, it is important to be taught as an effort to improve the order of life in everyday life both individually and in social life. It is in this context that the teachings of Sufism and morality become urgent to be implemented in Islamic Religious Education, this is in line with the main goal of Islamic Religious Education, which is to form pious and pious human beings personally and at the same time pious and pious socially.